EXPERIMENTAL AND NUMERICAL INVESTIGATION OF THE EFFECTS OF VORTEX FINDER GEOMETRY ON CYCLONE PERFORMANCE - Karadeniz, Aykut; Ayvaz, Coskun; Demir, Selami; Aksel, Murat; Saral, Arslan (YILDIZ TECHNICAL UNIV, 2020)
In this study, nine different vortex finders (VFs) were used for investigations on cyclone pressure drop and particle collection efficiency. The collection efficiencies dropped for larger and smaller vortex finder dimension (VFDs). The collection efficiency increased with increasing vortex finder lengths (VFL). This increase was more obvious and statistically meaningful for the smallest VFD. Pressure drop in cyclones were mainly a function of VFD and increased with decreasing VFD. These effects were also observed in Computational Fluid Dynamics (CFD) simulations. A performance map was built for the design of a VF optimized for the highest collection efficiency and the lowest pressure drop. Based on the experimental results, a mathematical model was developed, and the nickel inhibition constants (KNi) were found to be 8.75 mg/L.
Keywords: Cyclones; vortex finder; pressure drop; collection efficiency; computational fluid dynamics; FLOW; OPTIMIZATION; PRESSURE; GAS; SEPARATORS; SIMULATION; DESIGN; MODEL; INLET; Engineering